Geometria esférica para a formação de professores: uma proposta interdisciplinar - Pataki, Irene (2003)
This work concerns the inservice education of mathematics teachers. One of its aims is to propose, to teachers, a teaching sequence, with activities that show the interdisciplinary relationship that exists between spherical geometry and geography, forming interconnections between these domains, at the same time as contextualising the content to be considered and motivating learning in a way that articulates the object of study with reality. Another aim is to provide to the teachers involved reflections about aspects related to the teaching of spherical geometry. Based on the Theory of Didactic Situation developed by G. BROUSSEAU (1986), the research methodology Didactic Engineering of M. ARTIGUE (1988) and the theory of Britt-Mari BARTH (1993) concerning teacher education, we elaborate a teaching sequence, composed of a motivating problem-situation along with eight other activities involving notions of spherical geometry. We investigate the question: How can a teaching sequence permit the appropriation of a new domain spherical geometry and encourage educators to re-elaborate their thinking? Our research hypotheses assume that geometrical knowledge allows different perspectives about our world, that the apprehension of content can lead to changes in our behaviour as teachers and that the use of interdisciplinarity and contextualisation will establish connections between different fields of knowledge. The analysis of the results points to a change in the attitudes and values of the teachers, which confirms our research hypothesis and emphasises the importance of the methodology adopted, leading us to believe that some aspects of the geometry studies were learnt and became institutionalised knowledge